PENGARUH POLA ASUH ORANG TUA PERMISIF TERHADAP KECANDUAN PERMAINAN DARING YANG DIMEDIASI OLEH KESEJAHTERAAN PSIKOLOGIS - Butar Butar, Taruli Artha; Achmad, Rendy Alfiannoor; Shadiqi, Muhammad Abdan (Universitas Gunadarma, 2024)
Online game addiction among adolescents is currently a major concern for parents in Indonesia. The parenting style implemented by parents can be one of the factors that trigger online game addiction in adolescents, one of which is the permissive parenting style. The main aim of this study is to investigate the effect of permissive parenting style on online game addiction mediated by psychological well-being, referring to the I-PACE theory. The quantitative method was employed in the study and respondents were selected using the purposive sampling technique. Participants in this study were adolescents aged 16-20 years throughout Indonesia who were collected by distributing questionnaires via social media. Data were collected from 269 respondents who were analyzed using the mediation model regression technique by Hayes with PROCESS software on the IBM SPSS version 25 for Windows application. The results of this study indicated that psychological well-being did not significantly mediate the effect of a permissive parenting style on online game addiction. However, psychological well-being significantly predicted online game addiction directly. Meanwhile, a permissive parenting style significantly predicted online game addiction. Permissive parenting style also significantly predicted psychological well-being. The permissive parenting style of fathers has a stronger effect on online gaming addiction.